A better bipolar transistor for wireless ICs. - Geppert, L.
As the world unwires, the market for wireless communication chips has begun to soar. Now, a breakthrough by IBM researchers promises to unleash a new generation of low power wireless communication ICs by solving a problem that has plagued semiconductor specialists for years. The problem revolves around the so-called mixed signal chips, which contains both ordinary field-effect transistors and bipolar transistors. This article presents a better bipolar transistor for wireless communications ICs. It also demonstrates the first structure to allow high-speed, low power bipolar transistor on the same chip with the fastest, lowest power CMOS circuits. The fastest bipolar transistors contain germanium in their bases, which lets them run in excess of 350 GHz, which is much faster than the ordinary silicon bipolar devices.
Keywords: IBM; SOI; Bipolar transistors; Field-effect transistors; Germanium; Mixed signal chips; Power CMOS circuits; Silicon-on-insulator.; Wireless ICs; Wireless communication chips